2022
DOI: 10.7759/cureus.27750
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Parkinson's Disease: A Narrative Review

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative age-related disorder that affects the central nervous system (CNS) and is characterized by uncontrollable movements such as shaking, stiffness, and loss of balance and coordination. Depression is a common non-motor manifestation of PD, but unfortunately, depression remains unrecognized and often undertreated. The underlying pathophysiology of depression in PD is complicated, and many studies have been conducted to know the exact cause, but the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Depression is present in approximately 40 to 60% of patients with PD, and the presence of this symptom worsens the already poor quality of life of individuals with this disease [163][164][165][166][167]. It is important to note that depression, or other mood disorders, can occur prior to the onset of motor symptoms [168], and that early treatment of depression associated with PD can promote better acceptance of the signs of the disease [169,170].…”
Section: Depressionmentioning
confidence: 99%
“…Depression is present in approximately 40 to 60% of patients with PD, and the presence of this symptom worsens the already poor quality of life of individuals with this disease [163][164][165][166][167]. It is important to note that depression, or other mood disorders, can occur prior to the onset of motor symptoms [168], and that early treatment of depression associated with PD can promote better acceptance of the signs of the disease [169,170].…”
Section: Depressionmentioning
confidence: 99%
“…Depression is the most common neuropsychiatric disorder among people with PD and is related to the degeneration of monoaminergic neurotransmitter systems and fronto-cortical dysfunctions [ 135 ]. A case-control study confirmed that low fecal BA content and a decrease in the genera Roseburia , Romboutsia , and Prevotella were related to depressive symptoms in PD patients [ 136 ].…”
Section: Scfas and Non-motor Symptoms Of Pdmentioning
confidence: 99%
“…About the disease-specific risk factors for depression in PD there are scanty data with ambiguity validity. In some studies, was shown that severe disability, earlier age of onset, more on/off fluctuations, family history of PD, are risk factors [20], in other study the brain disturbance is another disk factor [21]. The influence of genetic factors is ambiguous.…”
Section: Risk Factorsmentioning
confidence: 99%